THE INFLUENCE OF INCENTIVE PROGRAM TOWARDS EMPLOYEE MOTIVATION - Miranti, Rina; Hidayat, Taufik (Academic Research Centre Services, 2015)
This study is focusing on the role of human resources by exploring the influence of incentive towards the work motivation. The method used in this research is quantitative research method. The primary and secondary data used by researchers obtained through direct observation to the Packing Section at PT. San Fu Indonesia, as well as making a questionnaire submitted to the management of the company to then be submitted to the employees of Packing Section as the subject of this study. The respondents were the employees with the total numbers of 65 employees. The result shown that the incentives to employees Packing Section PT. San Fu Indonesia according to the results of the responses of respondents is in the category of moderate (average). The work motivation description is also in the category of moderate (average). This can be seen from the highest to the lowest sub-variables. The sub variable needs for power (need for power) has the highest score compared with other indicators. While the lowest variable of work motivation is the need for achievement (need for achievement).